2022
DOI: 10.1177/00031348221103657
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Multimodal Sport Science-Based Prehabilitation Program on Clinical Outcomes in Abdominal Cancer Patients: A Cohort Study

Abstract: Background The potential for prehabilitation programs to impact clinical outcomes is uncertain in abdominal cancer patients due to the short window of time to intervene and the weakened state of the patients. To improve the effectiveness of prehabilitation intervention, a multimodal sports science approach was implemented. Methods Prior to cancer-related surgery, 21 patients participated in a 4-week exercise and nutrition prehabilitation program comprised of blood flow restriction exercise (BFR) and a sports n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 19 publications
0
48
0
Order By: Relevance
“…The second study analyzed the benefits of a 4-week multi-modal prehabilitation program combining exercise with B-Strong™ bands and a sports nutrition supplement in 21 patients with abdominal cancer ( Wooten et al, 2022 ). While the results of the study indicated a beneficial effect on reducing complications ( p = 0.03) and length of hospital stay (∼5.5 fewer days, p = 0.02) as well as a 58% increase in step count 5-day post-op ( p = −.043), the comparison group was retrospectively analyzed (n = 71) and underwent usual standard of care without BFR or sports supplementation.…”
Section: The Impact Of Lesser-known Cuff Features On Personalized Pre...mentioning
confidence: 99%
“…The second study analyzed the benefits of a 4-week multi-modal prehabilitation program combining exercise with B-Strong™ bands and a sports nutrition supplement in 21 patients with abdominal cancer ( Wooten et al, 2022 ). While the results of the study indicated a beneficial effect on reducing complications ( p = 0.03) and length of hospital stay (∼5.5 fewer days, p = 0.02) as well as a 58% increase in step count 5-day post-op ( p = −.043), the comparison group was retrospectively analyzed (n = 71) and underwent usual standard of care without BFR or sports supplementation.…”
Section: The Impact Of Lesser-known Cuff Features On Personalized Pre...mentioning
confidence: 99%
“…47 However, prehabilitation was not related to the incidence of serious complications, readmission rate, changes in hand grip strength, fear of falling, the mental component of QoL, fasting serum concentrations of myostatin, follistatin, or growth hormone. 46,47…”
Section: Multimodal Prehabilitation Before Cancer-related and Noncanc...mentioning
confidence: 88%
“…Furthermore, prehabilitation was associated with a shorter LOS ( P =0.02) with 5.5 fewer days (4.7±2.1 vs. 10.2±1.2 days) and decreased incidence of any complications ( P =0.03) compared with abdominal cancer patients who underwent usual preoperative care (n=71) 47. However, prehabilitation was not related to the incidence of serious complications, readmission rate, changes in hand grip strength, fear of falling, the mental component of QoL, fasting serum concentrations of myostatin, follistatin, or growth hormone 46,47…”
Section: Characteristics and Efficacy Of Multimodal Prehabilitationmentioning
confidence: 96%
See 2 more Smart Citations